Strategies for inclusion physical education for everyone - Lieberman, Lauren J. 1965-; Grenier, Michelle 1956-; Houston-Wilson, Cathy 1962- (Champaign, IL, USA Human Kinetics, 2025)
"The purpose of this book is to provide physical education teachers with the information and tools necessary for the successful inclusion of students with disabilities into their programs. This product is designed to serve as a higher education textbook as well as a professional development or continuing education resource"--Provided by publisher.
Inclusion in physical education -- Assessment : the cornerstone of effective instruction -- The placement process in physical education -- Individualized education plans -- Collaborative practice that promotes student engagement -- Positive interventions to manage behaviors and increase student performance -- Universal design for learning -- Support personnel -- Transition planning -- Basic skills -- Sport skills -- Health and fitness -- Recreation and life skills.
Includes bibliographical references and index.
Keywords: Physical education for children with disabilities -- United States; Physical education for children -- United States